Pengaruh Komponen Arus Kas Dan Laba Bersih Terhadap Harga Saham Studi Empiris Pada Perusahaan Asuransi Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2010-2014 - Marlina, Tri; Haryanto, Ryan Aprilla (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
This study aims to empirically examine the effect of components of c flow that consist of operating cash flow, investing cash flow, financing cash fl and net income to stock price on insurance companies in Indonesian Stock Exchange. This study used secondary data obtained from company financial reports from the period 2010 until 2014 insurance company that are listed in Indonesia Stock Exchange. The tests conducted were descriptive statistics, classic assumption test, multiple linear regression analysis, coefficient determination, F test, and t test with using the application program SPSS version 20 for windows. Simultaneous research results show that the operating cash flow, investing cash flow, financing cash flow, and net income significantly influence stock price. Partially, operating cash flow significantly influences stock price. Investing cash flow, financing cash flow, and net income do not have significant influence on stock price.